2003
DOI: 10.21273/jashs.128.3.0403
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and 1-Methylcyclopropene Alter the Postharvest Quality of Broccoli

Abstract: Fresh broccoli (Brassica oleracea L. Italica group) florets untreated or treated with 1 μL·L-1 1-methylcyclopropene (1-MCP) for 14 h, were stored at 12 °C with 0, 200, or 700 nL·L-1 ozone. Senescence parameters were evaluated after 0, 1, 2, 5, 8, or 12 days of storage. Treatment with 1-MCP delayed the yellowing of florets, and at day 5 the hue angle of 1-MCP treated florets was 116° (green) compared to 102° (yellow) for the control. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 30 publications
2
33
0
3
Order By: Relevance
“…Maximum CO 2 and C 2 H 4 concentrations were observed at the first day after packaging that decreased at the 3rd and 2nd days of storage at 8 °C to minimum levels (for CO 2 and C 2 H 4 , respectively) and showed little change thereafter. Similarly to our data, respiration of fresh‐cut lettuce and broccoli was not affected by immersion in ozonated water dips (20 mg/L) or exposed to 200 nL/L ozone gas, respectively (Beltran et al, ; Forney, Song, Fan, Hildebrand, & Jordan, ). In contrast, Zhang, Zhaoxin, Zhifang, and Xiang () observed a reduction of respiration rate in fresh‐cut celery after immersion in ozonated water 0.18 mg/L for 5 min.…”
Section: Resultssupporting
confidence: 89%
“…Maximum CO 2 and C 2 H 4 concentrations were observed at the first day after packaging that decreased at the 3rd and 2nd days of storage at 8 °C to minimum levels (for CO 2 and C 2 H 4 , respectively) and showed little change thereafter. Similarly to our data, respiration of fresh‐cut lettuce and broccoli was not affected by immersion in ozonated water dips (20 mg/L) or exposed to 200 nL/L ozone gas, respectively (Beltran et al, ; Forney, Song, Fan, Hildebrand, & Jordan, ). In contrast, Zhang, Zhaoxin, Zhifang, and Xiang () observed a reduction of respiration rate in fresh‐cut celery after immersion in ozonated water 0.18 mg/L for 5 min.…”
Section: Resultssupporting
confidence: 89%
“…The present study demonstrated that the treatment of harvested coriander with 0.68 mg/L O 3 for 10 min resulted in a higher sensory evaluation ranking, inhibition of chlorophyll degradation, and extended the shelf life of coriander, relative to the untreated control. These results are similar to those reported for O 3 ‐treated broccoli (Forney et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…This could be due to cut surfaces that promoted the leaching of organic matter from the product, e.g. from fresh‐cut green peppers or tissue damage if the dose of ozone was too high . Ozone would in that case rather react with organic matter than act as an antimicrobial agent, thus being less efficient against the microorganisms.…”
Section: Ozone As An Antimicrobial Agentmentioning
confidence: 99%